Decarbonylation of Salicylaldehyde Activated by p‐Cymene Ruthenium(II) Dimer: Implication for Catalytic Alkyne Hydrothiolation. Issue 27 (29th August 2016) - Modem, Sarangapani; Kankala, Shravankumar; Balaboina, Ramesh; Thirukovela, Narasimha Swamy; Jonnalagadda, Sreekantha B.; Vadde, Ravinder; Vasam, Chandra Sekhar
Abstract : A stoichiometric C–H activation/decarbonylation of salicylaldehyde by [(η 6 ‐ p ‐cymene)RuCl2 ]2 gave a carbonyl derivative [(η 6 ‐ p ‐cymene)RuCl(CO)(Ph‐O)] (1 ) without the use of CO gas. A variety of polar phosphines were then incorporated into compound1 to give new Ru II cationic catalysts, [(η 6 ‐ p ‐cymene)Ru(CO)(Ph‐O)L]BF4 (2 –8 ). These were used to catalyse the hydrothiolation of alkynes with a range of thiols in aqueous THF to give anti‐Markovnikov E ‐linear vinyl sulfides in high yields. Abstract : A serendipitously discovered stoichiometric C–H activation/decarbonylation of salicylaldehyde by [(η 6 ‐ p ‐cymene)RuCl2 ]2 gave [(η 6 ‐ p ‐cymene)RuCl(CO)(Ph‐O)] (1 ) without the need for external CO gas. Polar phosphines were incorporated into1 to give cationic Ru II catalysts2 –8 . These were used in the hydrothiolation of alkynes to selectively give anti‐Markovnikov E ‐linear vinyl sulfides in aq. THF.